An assessment of the Kenyan coastal artisanal fishery and implications for the introduction of fish aggregation devices - Mbaru, Emmanuel Kakunde (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2013)
The marine fishery in Kenya is predominantly small-scale and artisanal with about 11,000 fishers intensely fishing near shore coastal reefs using minimally selective fishing gears. A large majority (88%) of fishers use outdated equipment such as basket traps, beach seines, hand lines (hook and lines), fence traps, gillnets, spearguns and cast nets. Handmade canoes propelled by paddles (kasia) or sail power are used to access offshore waters, while only a few fishers have motorized boats. Although fishers along this coast know and express the potential of offshore fishing, most of them are disempowered and unable to access any of the largely untapped offshore pelagic resources. Using a unique dataset from four distinct coastal areas: Funzi-Shirazi bay area, Diani-Chale area, Mombasa-Kilifi north coast area and the Malindi-Ungwana bay area, containing species level length frequency catch data from the multi-gear and multi-species fishery, abundance of specific species, gear use comparisons in various regions, catch per unit effort and total catch estimate over a nine year period (2001 "“ 2009) were evaluated. Despite high diversity in the fishery, five species (Lethrinus lentjan, Siganus sutor, Leptoscarus vaigiensis, Lethrinus harak and Parupeneus macronemus) represented over 75% of the catch. A total of 11 legitimate gears were observed in this coastal artisanal fishery with basket traps (42%) being the most popular. Fishers along the Mombasa-Kilifi area predominatly used beach seines while those in Diani-Chale, Malindi-Ungwana bay and Funzi-shirazi bay predominaltly used spearguns, gillnets and basket traps, respectively. Apart from gillnets, a general declining trend for most of the gear types was observed since 2004. Beach seines recorded the lowest (20.9Â±0.2 cm) mean length while gillnets recorded the highest (34.2Â±0.3 cm). The highest catch (~26,000 metric tons) came in 2001 and the lowest (~15,000 metric tons) in 2005. The highest number of fishers was observed in 2008 while 2009 recorded the highest (4.8Â±2.3) mean number of hours per outing. The mean annual CPUE per region ranged from (1.5 kg.fisher-1.hr-1) in Diani-Chale to (1.0 kg.fisher-1.hr-1) in Malindi-Ungwana bay. Making use of questionnaire data, the attitudes towards offshore fishing strategies, FADs in particular, were evaluated. Some communities (about 25% in every location) were not even aware of FAD fisheries. With the imminent introduction of a FAD fishery in Kenya, it was concluded that, for this fishery to realize its full potential, training on FAD fishing techniques has to be done. Finally, effective management is necessary if small-scale fisheries are to continue providing food security for many poor coastal communities. Gear-based management in Kenya, although under represented and under studied, has the potential to be adaptive, address multiple objectives, and be crafted to the socio-economic setting. Management effectiveness in near shore fisheries has generally been evaluated at the scale of the fish community. However, community level indicators can mask species-specific declines that provide significant portions of the fisheries yields and income. This thesis seeks to identify ways in which the Kenyan artisanal fishery can be sustained and managed from within coastal communities, giving them the resources and education to effectively improve their lives. The introduction of a offshore FAD fishery and hence access to offshore pelagic species provides an opportunity to not only alleviate pressure on coastal resources but also to empower coastal communities and contribute to the growth of Kenya's national economy as a whole.
Keywords: Fisheries -- Kenya; Fishery management -- Kenya; Fish aggregation devices; Small-scale fisheries -- Kenya; Small-scale fisheries -- Economic aspects -- Kenya